ANALYSIS OF SATISFACTION LEVEL OF THE CAPA PALOH VILLAGE COMMUNITY WITH THE SIBANCEH TOLL COMPENSATION - Hamdani, Hamdani; Safrika, Safrika (ITScience (Information Technology and Science), 2023)
This study aims to determine the level of community satisfaction with the SIBANCEH toll compensation in Capa Paloh Village, Padang Tiji District, Pidie Regency. This study was conducted in March 2022. There were 42 samples from a population of 129 toll road compensation recipients in Capa Paloh Village, Padang Tiji District, Pidie Regency. Collecting data using questionnaires, interviews, and documentation. The method used is qualitative and descriptive analysis. Descriptive analysis technique, namely a technique for describing or explaining data related to the discussion, where this technique describes the toll compensation that occurred in Capa Paloh Village, Padang Tiji District. The results showed that the level of community satisfaction with the SIBANCEH toll compensation in Capa Paloh Village, Padang Tiji District, Pidie Regency was satisfied, because the people who used to have inadequate houses, with the payment of toll compensation, the houses have been renovated and after with the construction of the toll road, the area where they live is increasingly crowded and the population is growing. In addition, the people affected by land acquisition can use the compensation money recipients not only to buy houses or rice fields, but can also be used for business capital or the community's personal savings.